Relationship between wood texture and wood surface roughness : an empirical study - Tan, Zheng Shing (2019)
The wood surface roughness has become more important in wood industry in recent year due to the effect of profitability and production speed. Thus, this study was conducted with the key purpose to investigate the relationship of wood texture (pores size and pores distribution) and wood surface roughness of 3 common used timber species from different density group which is Balau, Dark Red Meranti and Rubberwood. This study also keens to find out the effect of wood texture on wood surface roughness before and after sanding. 30 samples defect-free were obtained and processed with sanding using 180 grit sandpaper. Roughness and anatomical structure were analysed using international method. The findings of correlation showed that both indicators of wood texture have positive relationship with the indicators of wood surface roughness, which are Arithmetic mean deviation of the profile, Ra and average maximum peak to valley of profile, Rz. In multiple linear regression, four models were built and all models showed impact of wood texture to the indicators of wood surface roughness. The results concluded that wood texture has minimum influence on wood surface roughness even it is before and after sanding.